From Exceptionalism to Relationality: Responding to Mandatory Reporting in Texas Anti-Trans Directives. Issue 1 (February 2023) - Harrell, Sam; Jordan, Sid; Wahab, Stéphanie
This manuscript responds to recent directives in Texas that would define the facilitation or provision of gender-affirming medical treatment for minors as "child abuse." Specifically, we focus on the use of these directives to widen the scope of mandatory reporting laws. We briefly discuss the politics of mandatory reporting and the strategic appropriation of feminist, anti-violence narratives. We then critically analyze social work resistance to the Attorney General's opinion through a lens of exceptionalism. Finally, we discuss abolition feminism as a guidepost for critically questioning our field's allegiance to mandatory reporting as an ethical and evidence-based practice.